Radical extrapleural pneumonectomy with bronchial fistula by pulmonary function test evaluation technique. (December 2021) - Marzban-Rad, Saeid; Bozorgmehr, Rama; Sattari, Parastesh; Azimi, Ghasem; Azimi, Ali
Abstract: Introduction: and importance: Pulmonary Function Tests (PFTS) is an important tool in the assessment of pulmonary pathologies and preoperative evaluation. Case presentation : A 54-year-old man with history of massive pleurisy in the left thorax, treated by placing chest tube and drainage of bloody effusion, was readmitted for epithelioid mesothelioma. He was then presented with pneumothorax due by a refractory bronchial fistula while having a plural catheter. Based on the consultation, the whole-body bone scan was conducted, and findings demonstrated epithelioid mesothelioma (stage 1) with the refractory fistula for which the patient was candidate for thoracic surgery. Decreased lung capacity was seen by Pulmonary Function Testing – PFTS. Clinical discussion: The novel PFTS Evaluation Technique was designed to measure the true pulmonary capacities in order to evaluate the pulmonary post-operative tolerance. In this technique the chest tube was placed for 4 weeks until the patient reaches mediastinal fixation then the measurements by PFTS were carried out in two steps. First, using an open chest tube and second, using a clamped chest tube. In both steps, the pulmonary capacities were measured and provided to the pulmonologist for consultation. Conclusion: In this case, after acquiring the approval of the specialist depended on PFTS after PFTS Evaluation Technique, the radical extra pleural pneumonectomy surgery was conducted, and the patient was discharged with a good general appearance and treated fistula. Highlights: PFTS is an important tool in the assessment of pulmonary pathologies and for preoperative evaluation. The patient with pulmonary fistula cannot undergo pneumonectomy surgery. The PFTS evaluation technique lead to improve the method of evaluating lung capacity tests. Mediastinal fixation is a suitable approach for patients with refractory fistula and lack of surgical tolerance.